THE EFFECT OF GUIDED READING STRATEGY ON JUNIOR HIGH SCHOOL STUDENTS’ READING COMPREHENSION - Juni Triana Sitompul (TRANSFORM : Journal of English Language Teaching and Learning, 2012)
This study aims at investigating the effect of Guided Reading Strategy on Junior High School Student Reading Comprehension. The population of this study was the students of SMP Swasta Kristen Immanuel on Jl. Slamet Riyadi No. 1 Medan, fifty eight students from the population was taken as the samples of the research. The sample was divided into two groups. The first group (29 students) as the experimental group, while the rest (29 students) as the control group. The experimental group was taught by using guided reading strategy . The instrument of collecting the data was multiple choice tests. To obtain the reliability of the test, the writer used the Kuder Richardson Formula (KR-21). The result of the study showed that the reliability of the test was 0.733. The data were analyzed by using t-test formula, the analysis showed that the score of the student in the experimental group was significantly higher than that of students in the level of control group at the level of significance 0,05 with the degree of freedom (df)56 the t-observed is 5.33  while the t-table is 1.671.therefore the null hyphothesis (Ho) is rejected and the hyphothesis alternative (Ha) is accept   Key Words: Guided, Reading Strategy, Reading Comprehension